Orchid biogeography and rarity in a biodiversity hotspot: the Southwest Australian floristic region - Phillips, Ryan; Brown, Andrew; Dixon, Kingsley; Hopper, Stephen (Lankesteriana: International Journal on Orchidology, 2015)
Understanding the drivers of orchid diversification and rarity may prove crucial to their conservation. The Orchidaceae is characterised by the presence of mycorrhizal endophytes and a diversity of pollination syndromes (Rasmussen 1995, Jersakova et al. 2006). The prevalence of pollination by deceit and the spe- cialised mycorrhizal relationships in some taxa have been implicated in the diversification of the family (Cozzolino & Widmer 2005, Otero & Flanagan 2006). Furthermore, interactions with habitat speciali- sation may act in concert with these attributes to play a critical role in orchid diversification (Gravendeel et al. 2004). The influence of these factors in determin- ing intrinsic rarity in orchids remains poorly known.